AB0154 MERTK AND THE RESOLUTION OF INFLAMMATION IN IGG4-RELATED DISEASE. (2nd June 2020) - Della Torre, E.; Rovati, L.; Monno, A.; Maehara, T.; Kaneko, N.; Lanzillotta, M.; Pedica, F.; Doglioni, C.; Pillai, S.; Manfredi, A.
Abstract : Background: IgG4-Related Disease (IgG4-RD) is characterized by fibrotic lesions, serum IgG4 elevation, and prompt response to glucocorticoids. B and T lymphocytes are considered the initiators of tissue inflammation in IgG4-RD, but the prominent stromal reaction observed at disease sites suggest that a dysregulation of processes involved in the resolution of inflammation could be pathologically relevant as well. Mer receptor tyrosine kinase (MerTK) and its ligands protein S (Pros1) have a pivotal role in the resolution of inflammation through the activation of a well-characterized signaling pathway that ultimately dampens the immune response and promotes the recovery of tissue function. MerTK and the processes involved in the resolution of inflammation have never been addressed in IgG4-RD. Objectives: To investigate MerTK involvement in the pathogenesis of IgG4-RD by evaluating (a) the expression of MerTK and of its endogenous ligands in IgG4-RD tissues; (b) the presence of circulating precursors of MerTK+ cells infiltrating IgG4-RD lesions in the peripheral blood of IgG4-RD patients; (c) the effects of immunosuppressive therapies on MerTK expression in IgG4-RD tissues. Methods: Three distinct cohorts of IgG4-RD patients were included in this study. 8 active patients were used for immunohistochemistry studies for MerTK expression. 16 IgG4-RD and 14 Sjögren syndrome patients, together with 6 control tonsils, were used for multicolor immunofluorescence studies and TissueQuest software quantification of the expression of MerTK, CD68, CD163, Pros1, Gas6, CD4, SLAMF7, CD19, IgG4, cleaved caspase-3. 10 untreated IgG4-RD patients were used to evaluate MerTK expression in circulating monocytes subsets and fibrocytes by flow cytometry. Results: MerTK was highly expressed in IgG4-RD affected organs. MerTK+ cells accounted on average for 16% (range 5-35%) of all cells in the tissue, and the majority of them expressed CD68, reflecting a monocyte-macrophage origin. 33.5 % (interquartile range (IQR) 26-41%) of MerTK+ cells co-expressed CD68 and CD163, while 30.5% (IQR 19-41.5%) expressed CD68 but not CD163. CD68+MerTK+ cells displayed two main morphological appearances, compatible with those of macrophages and of myofibroblasts. In addition, MerTK+ cell number was significantly increased in salivary glands from IgG4-RD patients compared to Sjögren syndrome (p < 0.0001). Circulating precursors of CD68+MerTK+ cells infiltrating IgG4-RD lesions were identified by flow cytometery in the peripheral blood of patients with active IgG4-RD as MerTK+ populations of intermediate monocytes, nonclassical monocytes and collagen expressing fibrocytes. MerTK ligand Pros1 was exposed on 52% (IQR 42-57%) of infiltrating B lymphocytes, 74% (IQR 54-89%) of infiltrating T lymphocytes, and, likely, on apoptotic cells that were detected in IgG4-RD tissues. CD68+MerTK+ cells were found in physical contact with Pros1+ cells in IgG4-RD lesions and their number decreased by 56% after successful treatment with rituximab. Conclusion: MerTK is abundant in IgG4-RD affected organs and is preferentially expressed on CD68+ macrophages and myofibroblasts that infiltrate IgG4-RD lesions. MerTK+ cells might interact with apoptotic cells and Pros1 expressing T and B lymphocytes in IgG4-RD tissues, leading to the persistent activation of processes involved in the resolution of inflammation and promoting the development of tissue fibrosis. Disclosure of Interests: None declared